Effect of alendronate and platelet-rich plasma in tendon-bones integration in sheep anterior cruciate ligament surgery - Tangkas Sibarani; Bambang Purwanto; Ambar Mudigdo; Brian Wasita (GarVal Editorial Ltda., 2024)
Context: Anterior cruciate ligament (ACL) reconstruction often faces challenges due to poor integration of the tendon with bone. Aims: To evaluate the potential benefits of alendronate and platelet-rich plasma (PRP) in enhancing tendon-to-bone osteointegration in ACL surgery. Methods: This was a post-test only control group experimental study with Ovis aries Linnaeus sheep as experimental animals. The sample was divided into four groups: the control group ACL reconstruction with calcaneal tendons given NaCl, the group given PRP, alendronate, and PRP and alendronate. Bone healing biomarkers (NF-kB, TNF-α, MMP-9, TGF-β1, and COL1A1) were examined through immunohistochemical analysis and histological studies to assess osteoblast counts and inflammatory tissue. Results: There was a statistically significant (p<0.05) increase in MMP-9 and osteoblast count after alendronate and PRP administration. Administration of alendronate and PRP also increased other variables, namely TNF-α, COL1A1, and the level of inflammation, although not statistically significant (p>0.05). The intervention did not affect NF-kB and TGF-β1 (p> 0.05). Conclusions: These results show that the administration of alendronate and PRP improves the healing of tendon-calcaneal ACL reconstruction surgery in sheep.